2015
DOI: 10.1017/s0021932015000292
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Menstrual Cycle Characteristics and Perceived Body Image: A Cross-Sectional Survey of Polish Female Adolescents

Abstract: The increasing prevalence of negative body perceptions among adolescent girls and the tendency towards wishing to be thinner have become a cultural norm in Western culture. Adolescent girls are particularly vulnerable to developing a negative body image due to physical and sexual changes occurring during puberty. This study aimed to evaluate the association between different measures of body image perceptions and different phases of the menstrual cycle after controlling for weight status and other potential co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…In the present study, the secondary sexual characteristics of puberty were associated with the ED screening, as in the study done by Scherer et al (2010) who also found an association between the presence of menarche, body dissatisfaction, and symptoms of ED. Kaczmarek and Trambacz-Oleszak (2015) found an association between body dissatisfaction and different phases of the menstrual cycle in adolescents aged 12 to 18 years, showing that puberty and the body modifications it brings often result in bodily dissatisfaction, which can serve as a risk factor for ED [27, 28]. …”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the secondary sexual characteristics of puberty were associated with the ED screening, as in the study done by Scherer et al (2010) who also found an association between the presence of menarche, body dissatisfaction, and symptoms of ED. Kaczmarek and Trambacz-Oleszak (2015) found an association between body dissatisfaction and different phases of the menstrual cycle in adolescents aged 12 to 18 years, showing that puberty and the body modifications it brings often result in bodily dissatisfaction, which can serve as a risk factor for ED [27, 28]. …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, ideal body image was associated with weight status and menstrual cycle phase, and negative body image was significantly associated with different phases of the menstrual cycle and increasing body weight status [42]. Moreover, Kaczmarek and Trambacz-Oleszak [42]…”
Section: Diagnostic Groups Type Of Associationmentioning
confidence: 95%
“…Apart from the developmental stage, it has been reported that EDs patients have a more negative subjective perception of menarche, pubertal body changes, and first sexual activities, as compared to healthy women [34,117]. Indeed, ideal body image was associated with weight status and menstrual cycle phase, and negative body image was significantly associated with different phases of the menstrual cycle and increasing body weight status [42]. Moreover, Kaczmarek and Trambacz-Oleszak [42]…”
Section: Diagnostic Groups Type Of Associationmentioning
confidence: 97%
See 1 more Smart Citation
“…Psychologists have made some attempt to examine the nature and function of embodied premenstrual change, reporting that body image “distortion”, reflecting perceived increase in size, and body dissatisfaction is higher in the premenstrual phase of the cycle in the “normal” female population who don’t self-position as PMS sufferers (Carr-Nangle, Johnson, Bergeron, & Nangle, 1994; Jappe & Gardner, 2009; Kaczmarek & Trambacz-Oleszak, 2016; Racine et al., 2012; Teixeira, Dias, Damasceno, Lamounier, & Gardner, 2013). In those women who do present with PMDs, levels of premenstrual symptom severity have been reported to be associated with body image disturbance (Muljat, Lustyk, & Miller, 2007) and with body dissatisfaction (Kleinstäuber et al., 2016).…”
Section: Researching Premenstrual Embodiment: Positivism Versus Critimentioning
confidence: 99%